The ESG Paradox in ASEAN Islamic Banking: Evidence From ESG Performance - Muslimin Muslimin; Sri Hasnawati; Mahatma Kufepaksi (PPJP ULM, 2026)
This study examines the ESG paradox in ASEAN Islamic banking, where Shariah compliance does not guarantee superior sustainability performance. Using pooled data from 53 listed banks across six ASEAN countries (2015 – 2024), the research analyses the determinants of ESG performance through pooled OLS regression with HAC estimators. Findings reveal an